The Impact of Economic Growth on the Environment: Evidence from Environmental Kuznet Curve Analysis in 7 ASEAN Countries - Pangestu, Nuhansyah Arga (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
Environmental degradation is one of the issues resulted from the economic development. ASEAN countries are no exception. As a new economic market', economic growth has affected environmental degradation. The basic theory of the relationship between economic growth and environmental degradation was introduced by Grossman and Krueger in 1991 by adapting the Kuznet Curve inequality theory published by Simon Kuznet in 1955. This theory, Environmental Curve Kuznet theory (EKC), posited that there is possibility of economic growth which could pose a positive impact on ecosystem and environmental improvement. This study tries to prove that EKC theory can occur in ASEAN countries. In addition, this study also aims to illustrate the position of turning point of inverted U-curve in ASEAN region and compare the real and estimated value of EKC theory of each country. Several variables used in the study are Gross Domestic Product per capita, added value of industrial sector, and percentage of urban population growth. These variables are used as a reference to prove the influence between economic growth and environmental degradation, as reflected by Carbon Dioxide (CO2) pollution variables. The results of this study shows that all economic variables have a significant impact on CO2 pollution levels. Furthermore, this study proves that there is a turning point where ASEAN countries will enjoy positive results from economic growth on the environment. Nevertheless, not all ASEAN countries are able to pass the point due to the close distance between the real and estimated value of EKC theory that rise annually.Keywords: environmental economics, Kuznet Kurve, Environmental Kuznet Curve, industrialization, urbanization, panel data regression, fixed effect modelÂ